2023
DOI: 10.1038/s41467-023-36620-y
|View full text |Cite
|
Sign up to set email alerts
|

Citrullination modulates antigen processing and presentation by revealing cryptic epitopes in rheumatoid arthritis

Abstract: Cryptic peptides, hidden from the immune system under physiologic conditions, are revealed by changes to MHC class II processing and hypothesized to drive the loss of immune tolerance to self-antigens in autoimmunity. Rheumatoid arthritis (RA) is an autoimmune disease characterized by immune responses to citrullinated self-antigens, in which arginine residues are converted to citrullines. Here, we investigate the hypothesis that citrullination exposes cryptic peptides by modifying protein structure and proteol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…To this end, a number of autoimmune diseases, including RA and MS, have been described to involve the citrullination of arginine. 71 Citrullination is carried out by peptidylarginine deiminases (PADs) and higher levels of citrullinated proteins have been found in older mice relative to young mice. 72 A shift in higher levels of citrullination past the full scope of negative selection could provide a pathway for autoreactivity.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, a number of autoimmune diseases, including RA and MS, have been described to involve the citrullination of arginine. 71 Citrullination is carried out by peptidylarginine deiminases (PADs) and higher levels of citrullinated proteins have been found in older mice relative to young mice. 72 A shift in higher levels of citrullination past the full scope of negative selection could provide a pathway for autoreactivity.…”
Section: Resultsmentioning
confidence: 99%
“…However, as mentioned earlier, citrullination robustly affects protein structure and folding [6,8,9], and research has confirmed that citrullination can regulate the processing of MHC-II antigens through the generation and destruction of epitopes, resulting in the loss of immune tolerance to citrullinated proteins. Moreover, most changes in antigen processing caused by citrullination lead to the generation of new or enhanced original antigenic epitopes, possibly leading to extensive alterations in the self-antigenic peptide repertoire produced by antigen-presenting cells (APCs) [18]. Citrullination is prevalent in autoimmune diseases and cancer, such as rheumatoid arthritis (RA) [42,43], diabetes [44,45], psoriasis [46], Alzheimer's disease (AD) [47][48][49], multiple sclerosis [12,50] and various cancers [13].…”
Section: Role Of Citrullination Modification In Immunomodulation Immu...mentioning
confidence: 99%
“…Additionally, hypercitrullinated MBP can also induce the differentiation of CD4 + T cells into Th17 cells, suggesting that citrullination may play a role in disrupting tolerance to this autoantigen [68]. The occurrence of autoimmune diseases is closely tied to the loss of immune tolerance, and by altering the structure and protein hydrolysis of citrullinated antigens, citrullination is believed to comprehensively modify antigen processing and presentation, promoting the generation and presentation of new cryptic epitopes capable of stimulating autoreactive T cells in RA patients [18]. Experimental evidence suggests that citrullination contributes to the breakdown of immune tolerance and may generate neoantigens, which can become additional targets during epitope spreading [69].…”
Section: Role Of Citrullination Modification In Immunomodulation Immu...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study further demonstrates that citrullination of vimentin and fibrinogen results in the generation of neoantigens composed of a native sequence of these two proteins. Such native neoantigens are able to activate T cells from ACPA + RA patients [52]. Emerging data have further suggested active pathogenic roles for some of the citrullinated ECM proteins in RA.…”
Section: Citrullination Of Extracellular Matrix Proteins In Human Dis...mentioning
confidence: 99%